Encouraging Parents to Participate in "KESGILUT” (Dental and Oral Health) Program Using "AWAS” (Aku Wedi Anakku Gigis) Educational Book - Zuhdi, Nadya Adina; Adla, Karina Awanis; Maharani, Gita Alethea Kristi; Karimah, Zalfa; Krissanti, Theresa Dian; Sembadani, Yuliana Merlindika; Kresna, Innocencio; Rachmawati, Almira; Nurrezeki, Andi Adani; Fionna, Callista Gladys; Syahdryani, Zhafira Putri; Setijanto, R. Darmawan (Indonesian Journal of Dental Medicine, 2020)
Background: A preliminary epidemiological study of three kindergartens in Embong Kaliasin Village under Ketabang Public Health Center, Surabaya coverage revealed that 63% of the kindergarteners have dental caries. The study also found that only 8% of them received dental treatment. The remaining 92% of kindergarteners never had dental treatment because uncovered health insurance, unavailability of parents during working days and hours, mother's education level, mother's medical history, paternal support in dental and oral health care. Promotive, preventive, and referral efforts can be achieved by empowering health cadres. The empowerment program addressed maternal reluctance in participating "KESGILUT” program by providing the "AWAS” educational book. Purpose: We expect that the program could increase mothers' knowledge levels on dental and oral health as well as encourage them to participate in child dental and oralhealth care. Methods: The health education method was parental mentoring with a group approach. The parents of Manguni kindergarteners receiving the "AWAS” educational book as a group. The media of the program was the "AWAS” educational book. It covered information about dental and oral health, including primary and secondary dentition, stages of dental caries, correct tooth brushing, nutritious food for teeth, and preventing dental caries. The evaluation method of this program is using pre-post test analysis. Results: There is an increasement in post test score (68%) to post-test score (83%). Conclusion: This program is effective to increase mother's knowledge about dental and oral health.